Factors Associated with Urinary Stress Incontinence in Primiparas - Pei-Ling Chou; Fang-Ping Chen; Li-Fen Teng (Elsevier, 2005)
Objective: To evaluate obstetric and maternal risk factors for stress urinary incontinence in primiparas. Materials and Methods: From January 2001 to August 2002, 378 primiparas were interviewed about stress urinary incontinence 1 year after delivery. The association between symptoms of urinary stress incontinence and obstetric factors was assessed. Results: Twenty-four (6%) primiparas had urinary stress incontinence after delivery. Maternal age was positively associated with urinary stress incontinence 1 year after delivery in primiparas who underwent vaginal delivery but not those who underwent cesarean section. There was a 4.5% greater prevalence of stress incontinence for each 5-year increase in age (coefficient B, 0.045; 95% confidence interval, CI, 0.04-0.51; p < 0.001). In primiparas who underwent cesarean section, performance of pelvic floor exercise was significantly related to a decrease in incontinence 1 year after delivery (odds ratio, 0.156; 95% CI, 0.034-0.713; p < 0.05). No such relationship was found in primiparas who underwent vaginal delivery. Body mass index, body weight gain during pregnancy, neonatal birth weight, head circumference, mode of delivery, and diabetes mellitus were not associated with stress incontinence 1 year after delivery in any primipara. Factors related to vaginal birth, including length of the first and second stages of labor, large perineal laceration, and instrumental delivery, also had no effect. Conclusion: For primiparas who underwent vaginal delivery, an increase in age was associated with increased risk of development of stress incontinence. Increased vulnerability of the pelvic floor with age might explain this finding. Pelvic floor exercise had a protective effect against postpartum stress incontinence in primiparas who underwent cesarean section. This reflects the fact that pregnancy per se carries a risk of stress incontinence. We recommend that primiparas perform pelvic floor exercises to prevent the development of postpartum stress incontinence.